2012
DOI: 10.1371/journal.pone.0029684
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Inference of Ancestry and Admixture Proportions through Ancestry-Informative Insertion Deletion Multiplexing

Abstract: Ancestry-informative markers (AIMs) show high allele frequency divergence between different ancestral or geographically distant populations. These genetic markers are especially useful in inferring the likely ancestral origin of an individual or estimating the apportionment of ancestry components in admixed individuals or populations. The study of AIMs is of great interest in clinical genetics research, particularly to detect and correct for population substructure effects in case-control association studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
230
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(259 citation statements)
references
References 51 publications
(71 reference statements)
7
230
0
13
Order By: Relevance
“…33,37 We concluded that this panel has accuracy and is suitable to estimate genetic ancestry in highly admixed populations such as the Brazilian. 33,37 Herein, we aimed to establish the QMVR of BAT-25, BAT-26, NR-21, NR-24, and NR-27 markers, in a Brazilian healthy population, to evaluate the feasibility of MSI status determination of tumors without the need of matching normal DNA. Furthermore, we intend to determine the ancestry of Brazilian individuals using specific AIMINDELs and correlate with their QMVR.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…33,37 We concluded that this panel has accuracy and is suitable to estimate genetic ancestry in highly admixed populations such as the Brazilian. 33,37 Herein, we aimed to establish the QMVR of BAT-25, BAT-26, NR-21, NR-24, and NR-27 markers, in a Brazilian healthy population, to evaluate the feasibility of MSI status determination of tumors without the need of matching normal DNA. Furthermore, we intend to determine the ancestry of Brazilian individuals using specific AIMINDELs and correlate with their QMVR.…”
Section: Introductionmentioning
confidence: 87%
“…[33][34][35][36] Some of these studies are focused on insertion deletion polymorphisms (INDELs) that are likely to be important factors underlying inherited traits in humans. 33 Recently, using a set of AIM-INDELs, we estimated the ancestry proportions of individuals from Amazonas, Belém, and Rio de Janeiro populations in Brazil. 33,37 We concluded that this panel has accuracy and is suitable to estimate genetic ancestry in highly admixed populations such as the Brazilian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significative differences in allele frequencies of InDel markers, between different groups or populations, can be used as ancestry and eventually, evolutionary indicators [13]. [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…La simplicidad de este enfoque proporciona un uso fácil y una elevada eficiencia en tiempo y coste [14]. Estos marcadores son capaces de distinguir de modo fiable la ancestralidad entre las principales poblaciones continentales de África, Europa, este de Asia y América [16]. Por último, proporcionan una capacidad superior para detectar mezclas de adn de individuos distintos, dado que en los electroferogramas producen patrones de picos mucho más equilibrados que los snp.…”
Section: Marcadores Informativos De Ancestralidad (Aim)unclassified